2019
DOI: 10.1111/asj.13272
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cell generation from bovine somatic cells indicates unmet needs for pluripotency sustenance

Abstract: Mechanisms that direct reprogramming of differentiated somatic cells to induced pluripotent stem cells (iPSCs), albeit incomplete in understanding, are highly conserved across all mammalian species studied. Equally, proof of principle that iPSCs can be derived from domestic cattle has been reported in several publications. In our efforts to derive and study bovine iPSCs, we encountered inadequacy of methods to generate, sustain, and characterize these cells. Our results suggest that iPSC protocols optimized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 61 publications
(142 reference statements)
3
19
0
Order By: Relevance
“…These cells, in general, however, lack the standard pluripotent stem cell criteria: poor derivation efficiencies; inability of maintaining pluripotency in long-term culture; limited developmental potential in the in vitro and in vivo assays such as chimera generation. The reported bovine iPSC lines often have leaky expression of the reprogramming genetic factors (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…These cells, in general, however, lack the standard pluripotent stem cell criteria: poor derivation efficiencies; inability of maintaining pluripotency in long-term culture; limited developmental potential in the in vitro and in vivo assays such as chimera generation. The reported bovine iPSC lines often have leaky expression of the reprogramming genetic factors (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…It has been reported that iPSCs can be established not only in humans and mice but also in several other animals [ 62 , 68 , 69 , 70 , 71 ]. Interestingly, the number of species for which iPSCs has be established is greater than the number of species for which ESCs can be established.…”
Section: Other Pluripotent Stem Cells In Cattlementioning
confidence: 99%
“…However, like their bESC counterparts, all these cells in general suffer limited self-renewal capacity. Also, most of the biPSCs, including those reported recently [ 19 , 20 ] still relied on the expression of exogenous transgenes for continuous propagation. Meanwhile, bovine trophectoderm cells were reported when reprogramed using conditions for biPSCs generation [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, bovine trophectoderm cells were reported when reprogramed using conditions for biPSCs generation [ 15 , 21 ]. The problems of persistent transgene activity [ 22 ], limited propagation capacity of the biPSCs [ 20 ], and the unexpected generation of trophectoderm-lineage stem cells [ 23 ] indicate that the majority of reported biPSCs were partially reprogrammed. Overall, the lack of completely reprogrammed biPSCs signifies the existence of unidentified reprogramming hurdles in bovine somatic cells that prevent the generation of bona fide biPSCs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%